Why Guattari? A Liberation of Cartographies, Ecologies and Politics - Jellis, Thomas; Gerlach, Joe; Dewsbury, John-David (Taylor & Francis, 2019)
This book examines Félix Guattari, the French psychoanalyst, philosopher, and radical activist, renowned for an energetic style of thought that cuts across conceptual, political, and institutional spheres. Increasingly recognised as a key figure in his own right, Guattari's influence in contemporary social theory and the modern social sciences continues to grow. From the ecosophy of hurricanes to the micropolitics of cinema, the book draws together a series of Guattarian motifs which animate the complexity of one of the twentieth century's greatest and most enigmatic thinkers. The book examines techniques and modes of thought that contribute to a liberation of thinking and subjectivity. Divided thematically into three parts - 'cartographies', 'ecologies', and 'micropolitics' - each chapter showcases the singular and pragmatic grounds by which Guattari's signature concepts can be found to be both disruptive to traditional modes of thinking, and generative toward novel forms of ethics, politics and sociality. This interdisciplinary compendium on Guattari's exciting, experimental, and enigmatic thought will appeal to academics and postgraduates within Social Theory, Human Geography, and Continental Philosophy.